Enhancing Problem-Solving Skills in Elasticity and Hooke’s Law through Problem-Based Learning with PhET Media and Mechanics Kits - Niko, Salma; Odja, Abdul Haris; S. Payu, Citron (Physics Education Research Journal, 2024)
This research was conducted in Class IX of SMA Negeri Posigadan. This research aims to determine the influence of the Problem-Based Learning model assisted by PhET media and Mechanics Kit on problem-solving ability in elasticity and Hooke's law. This research employs an experimental method. The population of this research comprises all grade IX students in the odd semester of SMA Negeri Posigadan for the academic year 2023/2024. The research sample was selected using random sampling, consisting of two classes: the experimental class, with 22 students applying the Problem-Based Learning model assisted by PhET media and mechanics Kit, and the control class, with 22 students applying the conventional model. Data for this research were obtained using test instruments in six essay questions. The results indicate that the experimental class received an average pretest score of 35.7 and an average post-test score of 82.1. Meanwhile, the control class obtained an average score of 31.3 and an average post-test score of 62.6. Both classes were found to have a normal distribution (obtained  and homogeneity (obtained . Subsequently, both classes were given different treatments, and a post-test was administered at the end of the lesson. From the statistical data analysis (one-tailed t-test), it obtained  or 5.031.68, indicating a significant influence of applying the Problem-Based Learning model assisted by PhET media and Mechanics Kit on problem-solving abilities in elasticity and Hooke's law.